Socioeconomic Determinants of Women’s Contraceptive Use in Indonesia 2020-2024 - Nadia Aprillia Agatha; I Wayan Suparta (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
High population growth is one of the development challenges in Indonesia, so the Family Planning (KB) program has an important role in controlling the growth rate. However, the participation rate of women in contraceptive use still shows interregional variations influenced by socioeconomic factors. This study aims to analyze the effect of the average length of women's schooling, women's labor force participation rate, GDP per capita, and the percentage of poor people on the percentage of women using contraception in Indonesia. This study uses a quantitative approach with regression analysis of panel data. The Data used is secondary data from 34 provinces in Indonesia during the period 2020-2024 sourced from the Central Statistics Agency. Analysis techniques include CHOW Test, Hausman test, classical assumption test, and hypothesis testing using t test, F test, and coefficient of determination with the help of EViews 12 application. The results showed that partially, GDP per capita and the percentage of poor people significantly affect the percentage of women who use contraception, with a negative influence. Meanwhile, the average length of women's schooling and the female labor force participation rate had no significant effect. However, simultaneously all independent variables significantly affect the use of contraception with a coefficient of determination of 97.51%. In conclusion, macroeconomic factors have a more dominant role than education and job participation in influencing contraceptive use. The implication is that government policies need to focus on improving public welfare, reducing poverty, and equitable access to reproductive health services in order to increase the effectiveness of family planning programs in Indonesia.